2022
DOI: 10.32479/ijeep.12875
|View full text |Cite
|
Sign up to set email alerts
|

Testing Environmental Kuznets Curve Hold in South Africa: An Econometric Approach

Abstract: The study investigates if the environmental Kuznets curve hold in South Africa. It employed available annual time series data spanning for the years from 1961 to 2020 collected from World Bank data. The study employs a Vector Error Correction Model (VECM) to investigate the short run and long run relationship. The results revealed that the Environmental Kuznets Curve hypothesis hold in South Africa. The policy recommendations are that the policymaker must implement environmentally friendly economic growth to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Anware (2014) assessed the same issue, and the study confirmed the findings of this current study that trade openness, GDP per capita, and FDI significantly affect tax revenue performance. Hlongwane et al (2022) found that tax revenue is positively affected by economic growth in the short run, while in the long run there is no effect. The current study, though it agrees with Hlongwane et al (2022) that tax revenue performance is positively affected by economic growth in the short run, disagrees on the long -run period.…”
Section: Results Of the Cointegration Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Anware (2014) assessed the same issue, and the study confirmed the findings of this current study that trade openness, GDP per capita, and FDI significantly affect tax revenue performance. Hlongwane et al (2022) found that tax revenue is positively affected by economic growth in the short run, while in the long run there is no effect. The current study, though it agrees with Hlongwane et al (2022) that tax revenue performance is positively affected by economic growth in the short run, disagrees on the long -run period.…”
Section: Results Of the Cointegration Testmentioning
confidence: 99%
“…He discovered that structural variables, which are exports and imports, have a significant impact on tax revenue. In the short run, economic growth has a positive impact on tax revenue, according to Hlongwane, Olebogeng, and Sithole (2022). Prowd and Kollie (2021) used monthly time series data and the VECM estimate technique to study the elements that are likely to drive tax revenue performance.…”
Section: Empirical Studies On the Determinants Of Tax Revenuementioning
confidence: 99%
“…The EKC has been examined in numerous telling scenarios, including air pollution emissions in a study by Selden and Song [97], carbon dioxide emissions in research by Arango Miranda et al [98], the impact of industrial construction on urban pollution from haze in the work of Wang et al [99], and waste discharge as reported by Ichinose et al [100]. There is research that provides evidence for the presence of the curve in some countries and for specific pollutants [101,102], whereas other studies [103] argue against its empirical accuracy.…”
Section: Determinants Of Ecological Footprintmentioning
confidence: 99%
“…In terms of regulatory frameworks, the collaborative process regulating oil and gas development in Colorado represents a potential model for regulating other emerging concerns, such as indoor air pollution from wildfires (Murphy et al, 2019). Environmental conservation policies, technological advancement, and modern industrial policies are recommended to effectively reduce CO2 emissions in East African countries (Hlongwane & Daw, 2022). Furthermore, ensuring the environmental safety of offshore Arctic oil and gas projects is emphasized to mitigate environmental risks (Dmitrieva et al, 2021).…”
Section: Future Outlook and Emerging Trendsmentioning
confidence: 99%